PEMROGRAMAN BERORIENTASI OBYEK UNTUK MENINGKATKAN KINERJA LAPORAN KEUANGAN PADA TOKO YK - Indra Ava Dianta; Desy Setyowati (Elkom : Jurnal Elektronika dan Komputer, 2019)
YK store is a UKM (small and medium enterprises) whose activities are buying and selling wholesale goods such as oil, spices, noodles, flour, coconut milk, pepper, and others in moderation (wholesale). YK store manager does not have a bookkeeping application system for the process of making financial reports in accordance with financial accounting standards, and there is no support system for merchandise inventory which supports buying and selling transactions. Information systems for managing merchandise needed by companies to determine value according to transactions, for financial statements will use a journal of eternal methods to buy and sell transactions then post them to the ledger and make financial reports for all businesses. Bookkeeping information system design using microsoft visual basic 6.0, xammp as a server and mysql as a database. The results obtained from this information system can contain reports obtained in accordance with the types and financial statements for business activities